Analysis of Speed and Connection When Accessing Information in Database - Muhammad Guruh Ajinugroho; Tubagus Maulana Kusuma; Suryarini Widodo (J I M P - Jurnal Informatika Merdeka Pasuruan, 2023)
Animality Vetama is a pet store and clinic that has implemented an integrated management system which consist of several interconnected applications and a database across branches. Several branches complained about performances. Several factors was analyzed by the developer, resulting in a hypothesized that the problem was caused by connectivity issues on specific internet provider dubbed â€œprovider Xâ€. Said problem is suspected to lies within the TCP port because it only occurs when accessing the system but not when doing other things like browsing. Client application connects to the database using MySQL direct connection. To prove this case, a study using purposive sampling quota approach was proposed to determine what makes a problematic provider. This approach was then followed by a simulation for each criteria by doing a test connection to the database using the existing method and a proposed method using webservice. The simulation were focused on average connection durations as well as success and failed ratio. The result shown that in general, connecting to the database using webservice is a lot time faster than connecting client directly regardless of the provider. The success ratio is also increased significantly